2021
DOI: 10.1007/s40171-021-00283-9
|View full text |Cite
|
Sign up to set email alerts
|

Market Mechanisms for Reducing Emissions and the Introduction of a Flexible Consumption Tax

Abstract: Since its founding institutions the European Economic Community and Eratom, the European Union has paid great attention to energy issues. However, its powers have been updated in relatively recent times. Similarly, the EU has promoted in the post-Kyoto Protocol environmental issues with a leading by example approach and implementing an ambitious plan to decarbonize the economy with the energy transition and emission limitation through a market instrument, the emission trading system. The European emissions tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…This study confirmed how flexibility moves toward the SDGs. Previous studies highlight the positive relationship between sustainability and resilience within decisionmaking processes in risk measurement (Settembre-Blundo et al, 2021); of the potential benefits associated with the implementation of a flexible consumption tax (Gerbeti, 2021); of the decisive contribution of renewable energy globally (Ikram, 2021); and in the resilience of the education sector following pandermia (Ahmed et al, 2021).…”
Section: Results Discussion and Implicationsmentioning
confidence: 99%
“…Many developed countries, including the USA and UK, are heavily intervening in their green energy sectors (Allan et al, 2021). Moreover, with growing use border taxes on carbon (for example, the EU (Gerbeti, 2021)), supporting and greening economies will reduce taxes and bring market advantage, while achieving climate targets.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Jakob [36] argues that if major emitters worldwide apply the CBAM, competitiveness in international trade will be eliminated, which will incentivize other economies to adopt low-carbon strategies. Gerbeti [37] illustrates that the CBAM is an effective way to reduce emissions while maintaining the EU's industrial competitiveness. Thube et al [38] suggest that the CBAM can incentivize countries that have not implemented carbon pricing policies yet to join the climate club.…”
Section: Literature Reviewmentioning
confidence: 99%